The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/ijcs.12867
|View full text |Cite
|
Sign up to set email alerts
|

The impact of age stereotype threats on older consumers' intention to buy masstige brand products

Abstract: This study explores the relationship between old‐age stereotyping and older consumers' masstige product consumption, specifically, their intention to purchase masstige brand products, with a focus on their motivational drives from an identity‐signaling perspective. We surveyed 533 people aged 54 to 64 years in South Korea. Structural equation modeling was used to analyse the mediating effect, and hierarchical regression analysis was applied to test the moderating effect. Our results indicated that among older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 137 publications
0
12
0
1
Order By: Relevance
“…Empirical research on consumption behaviour has shown that brand value positively influences consumers' purchase intention (Buil et al, 2013; Walter et al, 2022). Bae and Jo (2022) proved that if a brand has an image characterized by old‐age stereotyping, the value of masstige mediates the relationship between these characteristics and intention to purchase masstige brands. The linear relationship between overall brand value and purchase intention has been investigated in the context of masstige brands (Park et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical research on consumption behaviour has shown that brand value positively influences consumers' purchase intention (Buil et al, 2013; Walter et al, 2022). Bae and Jo (2022) proved that if a brand has an image characterized by old‐age stereotyping, the value of masstige mediates the relationship between these characteristics and intention to purchase masstige brands. The linear relationship between overall brand value and purchase intention has been investigated in the context of masstige brands (Park et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The existing literature offers diverging insights into the value of self-identification within masstige consumption. While some studies suggest that masstige consumers might display a relatively lower interest in self-expression and shaping their self-image through consumption choices (Hudders et al, 2013;Kola nska-Stronka & Krasa, 2023), Bae and Jo (2022) document a notable impact of a desirable identity on masstige purchase intentions, citing a distinct motivation to dissociate from an "old-age" group as a significant motivation for masstige buying, particularly in South Korea. Also, Das, Saha, Jebarajakirthy, et al (2022c) illustrate the role of cultural identity on individuals' perception of masstige brands.…”
Section: Masstige Buyersmentioning
confidence: 99%
“…Long-term happiness is an important construct for discussion within the masstige context, as consumers can build long-term relationships with masstige brands (Nobre et al, 2022). The intention to purchase is another important construct to investigate to better understand the consumption of masstige products (Bae & Jo, 2022).…”
Section: Happiness and The Intention To Purchase A Masstige Productmentioning
confidence: 99%
“…Therefore, it is important to investigate happiness within the masstige context, as it concerns social display and recognition (Purohit & Radia, 2022). However, whether short‐term happiness leads to the intention to purchase a masstige product has not been the focus of previous studies on both happiness (Mansoor & Paul, 2022; Rodrigues et al, 2022) and the intention to purchase (Bae & Jo, 2022).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation